Economic growth and trend changes in wildlife hunting - Yukichika KAWATA (Acta Agriculturae Slovenica)
Petty-Clark’s law suggests that as the economy of a country develops, its proportion of primary industries declines while those of its secondary and tertiary industries increase.  Traditionally, hunting has played a crucial role in a country’s food supply; however, currently, it is increasingly viewed as a leisure activity. This paper empirically examines whether Petty-Clark’s law holds in case of hunting in European countries.  The results reveal that the proportion of hunters across countries increases when the per capita GDP is between 5,000 and 15,000 USD. Once the per capita GDP crosses the 15,000 USD mark, two major trends are detected: the number of hunters continues to increase in some countries but decreases in some other countries. Finally, the number of hunters in a country stabilizes when its per capita GDP reaches around 25,000 to 30,000 USD.